Atomic Layer Deposition of Al2O3 Directly on 2D Materials for High‐Performance Electronics. Issue 10 (18th March 2019) - Li, Na; Wei, Zheng; Zhao, Jing; Wang, Qinqin; Shen, Cheng; Wang, Shuopei; Tang, Jian; Yang, Rong; Shi, Dongxia; Zhang, Guangyu
Abstract: Due to the lack of surface dangling bonds of 2D materials such as graphene, hexagonal boron nitride, MoS2 etc., deposition of high‐κ dielectrics directly on such 2D materials by atomic layer deposition (ALD) is difficult and a nucleation layer is usually required. Here an ALD approach is developed to deposit high‐κ dielectric layer, e.g., Al2 O3, directly on 2D materials without the aid of the nucleation layer or introducing structural damages. In this approach, an individual deposition cycle includes one incremental organometallic pulse and multiple H2 O pulses to guarantee the uniform deposition of high‐quality high‐κ dielectric layers on graphene, MoS2, and other 2D materials directly. Large‐scale top‐gated MoS2 field‐effect transistors (FETs) with Al2 O3 as dielectric layers exhibit excellent performances including high on/off ratio exceeding 10 8 and mobility up to 70 cm 2 V −1 s −1 . The high‐quality Al2 O3 layer is also integrated into MoS2 based flexible FETs and inverters, and a significant voltage gain of 412 is obtained. This ALD approach also works for other materials like gold with inert surfaces, showing great promise for novel electronics. Abstract : A modified atomic layer deposition approach in which one cycle includes one incremental organometallic pulse and multiple H2 O pulses is developed to directly deposit uniform and high‐quality high‐κ dielectric layer on chemically inert 2D materials without introducing any structural damages. The Al2 O3 layer is integrated into MoS2 based flexible devices and exhibit excellent performances, indicating this approach is compatible for 2D material electronics.